PENERAPAN MODEL DISCOVERY LEARNING DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS IPAS SISWA SDN 20 TURATEA KAB. JENEPONTO - Aisya; Yumriani; Lukman Ismail (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The main problem in this study is how the application of the Discovery Learning model in improving the critical thinking skills of students in science at SDN 20 Turatea, Turatea District, Jeneponto Regency. This study aims to improve the critical thinking skills of students in science at grade V of UPT SDN 20 Turatea, Jeneponto Regency. This type of research is classroom action research (CAR) consisting of two cycles where each cycle is carried out for four meetings. The research procedures include planning, implementation of actions, observation, and reflection. The subjects in this study were 26 students in grade V of UPT SDN 20 Turatea, Jeneponto Regency. The results of this study indicate that in the first cycle that was completed individually from 26 students, only 7 or 27% met the criteria for achieving learning objectives (KKTP) or were in the low category. Classically, it has not been met because the average value obtained was 40.3%. Meanwhile, in cycle II, out of 26 students, 23 or 88% have met the learning objective achievement criteria (KKTP) and classically, the average value obtained is 83% or is in the very high category. Based on the results of the study above, it can be concluded that the learning outcomes of class V Science at UPT SDN 20 Turatea, Jeneponto Regency through the application of the Discovery Learning model have increased.